The Electronic Structure of Mn in Oxides, Coordination Complexes, and the Oxygen-Evolving Complex of Photosystem II Studied by Resonant Inelastic X-ray Scattering - Glatzel, Pieter (2004)
Resonant inelastic X-ray scattering (RIXS) was used to collect Mn K pre-edge spectra and to study the electronic structure in oxides, molecular coordination complexes, as well as the S(1) and S(2) states of the oxygen-evolving complex (OEC) of photosystem II (PS II). The RIXS data yield two-dimensional plots that can be interpreted along the incident (absorption) energy or the energy transfer axis. The second energy dimension separates the pre-edge (predominantly 1s to 3d transitions) from the main K-edge, and a detailed analysis is thus possible. The 1s2p RIXS final-state electron configuration along the energy transfer axis is identical to conventional L-edge absorption spectroscopy, and the RIXS spectra are therefore sensitive to the Mn spin state. This new technique thus yields information on the electronic structure that is not accessible in conventional K-edge absorption spectroscopy. The line splittings can be understood within a ligand field multiplet model, i.e., (3d,3d) and (2p,3d) two-electron interactions are crucial to describe the spectral shapes in all systems. We propose to explain the shift of the K pre-edge absorption energy upon Mn oxidation in terms of the effective number of 3d electrons (fractional 3d orbital population). The spectral changes in the Mn 1s2p(3/2) RIXS spectra between the PS II S(1) and S(2) states are small compared to that of the oxides and two of the coordination complexes (Mn(III)(acac)(3) and Mn(IV)(sal)(2)(bipy)). We conclude that the electron in the step from S(1) to S(2) is transferred from a strongly delocalized orbital.